Threads and Strings: Interweaving Bhutanese traditional music, textiles and STEM - Som, Gurung; Westman, Johan; Wangmo, Tashi; Dorji, Tshering; Namdel, Ugyen; Phuntsho, Thinley (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
Science, Engineering, Technology and Mathematics (STEM) plays a significant role in preserving traditional culture and values in Bhutan. Harnessing the power of technology, Paro College of Education initiated the following projects to engage faculty and students: Traditional Music and STEM education Traditional Textile and STEM education Blending technology, specifically using Arduino programming, in crafting traditional musical instruments encourage deeper insights and understanding of sounds, pitch, rhythms, notations and codes. Textile weaving encompasses a series of processes including design-thinking and involving measurements, patterns, geometry, colours, design and assembly of looms. The student volunteers for the project were engaged in hands-on activities about textile and music beyond the classroom. The students enjoyed crafting musical instruments and textile weaving experiences applying their skills and integrating STEM in the processes. The annual STEM festival is an avenue to reach out to the schools, academia and industry. The Heritage Education and Professional Development Centre (HEDPC) empowers future teachers in Bhutan to cascade the knowledge, skills and values to foster a sustainable and dynamic rich Bhutanese culture.